Existence of Weak Solutions for A Class of Nonuniformly Nonlinear Elliptic Equations of p-Laplacian Type - Afrouzi, G. A.; Naghizadeh, Z.; Mirzadeh, F. (Communications in Mathematics and Applications, 2011)
The goal of this paper is to study the existence of non-trivial weak solutions for the nonuniformly nonlinear elliptic equation in an unbounded domain. The solution will be obtained in a subspace of the Sobolev space and the proofs rely essentially on a variation of the mountain pass theorem.